From compliance to competitiveness: MSME adaptation to the VAT rate increase in Jakarta - Adelia, Miska; Firmansyah, Amrie (Educoretax, 2025)
This study examines the responses of Micro, Small, and Medium Enterprises (MSMEs) in Jakarta to the increase in Value Added Tax (VAT) rates, focusing on administrative challenges and pricing strategies to maintain competitiveness and business sustainability. A qualitative design was employed using content analysis of secondary data. It comprised nine peer-reviewed journal articles published between 2020 and 2025 obtained through Google Scholar, and six tax regulations purposively selected for their relevance to VAT reform. The findings indicate that MSME responses are primarily determined by their regulatory understanding, digital readiness, and capacity to adapt to fiscal changes. Key challenges include low tax literacy, difficulties operating e-invoicing systems, and limited comprehension of Taxable Entrepreneur (PKP) obligations. The complexity of digital administration remains a significant barrier, particularly for enterprises with limited technological capacity. To mitigate fiscal pressures, MSMEs adopt various pricing strategies supported by cost efficiency, digitalization, and sound financial planning. The study recommends that the Directorate General of Taxes simplify VAT reporting procedures, strengthen adaptive tax education, and expand digital infrastructure. Meanwhile, MSMEs are encouraged to enhance financial management and technological readiness. Future research should incorporate primary data collection to provide richer contextual insights into MSME adaptation to taxation reforms.